2014
DOI: 10.1245/s10434-014-4036-4
|View full text |Cite
|
Sign up to set email alerts
|

The 90-Day Mortality After Pancreatectomy for Cancer Is Double the 30-Day Mortality: More than 20,000 Resections From the National Cancer Data Base

Abstract: Mortality rates within 90 days after pancreatic resection are double those at 30 days. The volume-outcome relationship persists in the NCDB. Reporting mortality rates 90 days after pancreatectomy is important. Hospitals should be aware of their annual volume and mortality rates 30 and 90 days after pancreatectomy and should benchmark the use of high-volume hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
101
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(114 citation statements)
references
References 10 publications
12
101
1
Order By: Relevance
“…Despite increasing resection rates in the course of our study, 30-day postoperative mortality slightly decreased in elderly patients who underwent resection for pancreatic or periampulary carcinoma. Thirty-day postoperative mortality in octogenarians (7.7%) in our study was in line with previous population-based and multi-institutional studies showing a (30-day and/or in-hospital) postoperative mortality between 4.7% and 15.5% [3,4,10]. In concordance with a large observational study of patients undergoing pancreatoduodenectomy for cancer [12], short-term mortality risk of octogenarians in our study did not differ from that of other elderly age groups.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Despite increasing resection rates in the course of our study, 30-day postoperative mortality slightly decreased in elderly patients who underwent resection for pancreatic or periampulary carcinoma. Thirty-day postoperative mortality in octogenarians (7.7%) in our study was in line with previous population-based and multi-institutional studies showing a (30-day and/or in-hospital) postoperative mortality between 4.7% and 15.5% [3,4,10]. In concordance with a large observational study of patients undergoing pancreatoduodenectomy for cancer [12], short-term mortality risk of octogenarians in our study did not differ from that of other elderly age groups.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, possibly more elderly patients in the Netherlands could benefit from pancreatic surgery [2,10]. Several studies on surgical risks of patients with gastrointestinal cancers showed that postoperative mortality prolonged beyond the 30-day postoperative period [3,[19][20][21]. In a recent study, a doubling of the 30-day mortality rate after pancreatic surgery was found by 90 days postoperative [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In is worth to mention however that even nowadays the mortality after pancreatectomies is not nil, particularly after pancreatico-duodenectomies. Thus, Swanson and co-workers have shown that the 90-day mortality after pancreatic resections for cancer is double the 30-day mortality (7.4% vs. 3.7%) (20).…”
Section: Resectable Pdacmentioning
confidence: 99%